2011
DOI: 10.5653/cerm.2011.38.2.87
|View full text |Cite
|
Sign up to set email alerts
|

Effect of artificial shrinkage on clinical outcome in fresh blastocyst transfer cycles

Abstract: ObjectiveThis study aimed to determine the safety and clinical effect of artificial shrinkage (AS) in terms of assisted hatching of fresh blastocysts. Also, we evaluated the correlation between patient age and the effect of AS on clinical outcome.MethodsTwo AS methods, using a 29-gauge needle and laser pulse, were compared. Seventy-three blastocysts were shrunk using a 29-gauge needle and the same number of other blastocysts were shrunk by a laser pulse. We evaluated the shrunken blastocysts hourly and conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Contrary to what we saw in this study, several authors found that survival rates, and subsequent implantation and birth rates were higher when the degree of blastocoele expansion was high and when an artificial collapse of the blastocoele cavity was induced before vitrification 13,29,[31][32][33] . Blastocoele collapse can be achieved mechanically by aspiring the blastocoele liquid with a micropipette or by inducing a releasing of this liquid using a laser shot 22,34 . Several studies have shown that high-quality early blastocyst embryos (G1 and G2) do not systematically develop to viable fully expanded blastocyst able to hatch and implant 29,32,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to what we saw in this study, several authors found that survival rates, and subsequent implantation and birth rates were higher when the degree of blastocoele expansion was high and when an artificial collapse of the blastocoele cavity was induced before vitrification 13,29,[31][32][33] . Blastocoele collapse can be achieved mechanically by aspiring the blastocoele liquid with a micropipette or by inducing a releasing of this liquid using a laser shot 22,34 . Several studies have shown that high-quality early blastocyst embryos (G1 and G2) do not systematically develop to viable fully expanded blastocyst able to hatch and implant 29,32,35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several factors can influence blastocyst re‐expansion, including vitrification technology and embryonic parameters. The AS technique is considered an effective method to restore the blastocoele and improve the efficiency of vitrification and clinical pregnancy rates . Desai et al .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of blastocysts, TPN embryos were transferred on day 3 of development from IVF-20 TM drops to CCM TM (Scandinavian IVF, EMB, Barcelona, Spain) drops and cultured in the aforementioned conditions for three additional days. On day 6 of development, 62 TPN-derived hatched blastocysts were selected and their blastocoel artificially shrunken by a laser pulse [22,23,33] before being assigned at random to one of the three storage periods (0 h, 24 h or 48 h).…”
Section: Origin Of Tripronucleated Embryos and Blastocystsmentioning
confidence: 99%